Chapter In defense of [the word] niewiasta - Sobczykowa, Joanna (Wydawnictwo Uniwersytetu Łódzkiego, 2024)
The article is a reflection on the stylistic status of the lexeme niewiasta in contemporary Polish — in connection with the text in „Tygodnik Powszechny” 2019 Niewiasty, wiejadła i inni winowajcy, which criticizes a term that is lofty, sublime in the biblical style. It takes into account dictionary qualifications and translation solutions of selected biblical places in four translations and the viability of this lexeme in religious and secular language. It touches upon the aspect of language and religious culture and suggests that the term sublime should be kept in the most important places in the Bible.